Comparative Effect Of Topical Sucralfate Cream On Wound Size In Sprague–Dawley Rats With Second-Degree Burns - Vrenda Alia; Triasari Oktavriana; Prasetyadi Mawardi; Muhammad Eko Irawanto; Arie Kusumawardani (Green Publisher Indonesia, 2026)
Background: Second-degree burns result in significant tissue damage and require optimal management to prevent complications and delayed healing. Silver sulfadiazine (SSD) is widely used as a standard topical therapy for burn wounds. Topical sucralfate has cytoprotective properties and has been suggested to enhance wound healing, making it a promising adjuvant therapy in wound management. Objective: To compare the reduction in second-degree burn wound size following treatment with 10% sucralfate cream, 7% sucralfate cream, and silver sulfadiazine in a rat model Methods: This experimental study employed a post-test only control group design using 48 Sprague Dawley rats with standardized second-degree burn injuries. The subjects were randomly allocated into four groups: Negative control with no treatment (NC), positive control with silver sulfadiazine (PC), treatment group with 7% sucralfate cream (T1), treatment group with 10% sucralfate cream (T2). Wound size was evaluated on days 1, 3, 7, and 14 using digital photographic analysis. Results: A statistically significant difference in wound size reduction was observed among the groups on day 14 (p < 0.001). The 10% sucralfate group (T2) demonstrated the greatest wound reduction, with a mean wound diameter of 44.62 ± 21.43 mm, which was comparable to the silver sulfadiazine group (48.89 ± 10.41 mm). Both groups showed significantly smaller wound sizes compared to the 7% sucralfate group (281.35 ± 99.33 mm) and the negative control group (936.48 ± 159.71 mm). Conclusion: The second-degree burn wound size in the 10% sucralfate group was smaller compared to the 7% sucralfate and silver sulfadiazine groups.